Analyzing the Drivers of the Strategies Adoptions to Increase Customer Value in Agile Software Development: An Empirical Study - Sambinelli, Fernando; Borges, Marcos A. F. (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2019)
Agile Software Development (ASD) has been widely accepted in the software industry as a means to increase customer value, despite the few empirical studies related to the subject. A recent systematic review study, based on academic works and industry experiences, mapped a set of strategies to increase customer value in the ASD. However, the factors that drive the adoption of these strategies were not mentioned. Based on a survey of 378 software professionals from 123 software-intensive companies in Brazil, we examined the associations of these strategies mapped to six drivers, including the team context (product type, product owner type and customer type) and the context of the organization (size of unit, level of agile adoption and agile experience). The results showed that the organizational context's driving factors are associated with the adoption of a more significant number of strategies than the factors related to the team context, focusing mainly on large companies, with 100% of the teams using agile methods and with having used ASD for more than five years.